Handbook of transportation science (New York : Kluwer Academic, 2003)
Over the past thirty-five years, a substantial amount of theoretical and empirical scholarly research has been developed across the discipline domains of Transportation. This research has been synthesized into a systematic handbook that examines the scientific concepts, methods, and principles of this growing and evolving field. The Handbook of Transportation Science outlines the field of transportation as a scientific discipline that transcends transportation technology and methods. Whether by car, truck, airplane - or by a mode of transportation that has not yet been conceived - transportation obeys fundamental properties. The science of transportation defines these properties, and demonstrates how our knowledge of one mode of transportation can be used to explain the behavior of another. Transportation scientists are motivated by the desire to explain spatial interactions that result in movement of people or objects from place to place. Its methodologies draw from physics, operations research, probability and control theory.
Transportation Science -- Transportation Science -- Human Elements in Transportation -- Discrete Choice Models with Applications to Departure Time and Route Choice -- Activity-Based Modeling of Travel Demand -- Transportation Safety -- Flows and Congestion -- Transportation Queueing -- Traffic Flow and Capacity -- Automated Vehicle Control -- Traffic Control -- Spatial Models -- Continuous Space Modelling -- Location Models in Transportation -- Routing and Network Models -- Network Equilibrium and Pricing -- Street Routing and Scheduling Problems -- Long-Haul Freight Transportation -- Airline Crew Scheduling -- Supply Chains -- Economic Models -- Revenue Management -- Spatial Interaction Modeling -- Principles of Transport Economics.
Elektronická reprodukce.
Keywords: doprava; dopravní výzkum; transportation; transportation research; kolektivní monografie; elektronické knihy; e-knihy online; collective monographs; electronic books; e-books online